Resolving the Speciation Patterns and Evolutionary History of the Intercontinental Disjunct Genus Corylus (Betulaceae) Using Genome-Wide SNPs - Yang, Zhen; Zhao, Tian-Tian; Ma, Qing-Hua; Liang, Li-Song; Wang, Gui-Xi (Frontiers in Plant Science, 2018)
Understanding the underlying mechanisms of species origin, divergence and distribution patterns of the intercontinental disjunct taxa has long fascinated botanists. Based on 4,894 genome-wide SNP (single nucleotide polymorphism) dataset, we present a molecular phylogenetic reconstruction of genus Corylus (Betulaceae), which have a disjunct distribution between Eurasia and North America. The aim is to explore the speciation patterns and evolutionary relationships of Corylus species by establishing a general phylogenetic framework with extensive sampling. Both the molecular phylogeny inferred from recombination-free dataset and structure analysis support the division of Corylus into four major clades (A-D). Recombination tests and hybridization detection reveal extensive recombination and hybridization events among different clades, which have potentially influenced the speciation process of Corylus. Divergence time estimation indicates that recent common ancestor (MRCA) of Corylus occurred in late Eocene (~36.38 Ma) and subsequent rapid diversification began during Miocene. Ancestral area reconstruction shows that Corylus originated from southwest China. The arrival of two clades (Clade B and C) to North America was well supported by the long distance dispersal (LDD) crossing the Bering land bridge (BLB). The Himalayas, European-Mediterranean area, and other distribution regions are primarily the recipients of dispersal taxa. Vicariance after dispersal plays an important role in speciation.